Spanish Energy Market: Overview Towards Price Forecast - Perez-Mora, Nicolas; Alomar, Miquel L.; Martinez-Moll, Victor (International Journal of Energy Economics and Policy, 2018)
This paper aims to give an overview of the Spanish Electric Market. This energy market is liberalized and complex due the new and modified rules along time. Due these circumstances the hourly energy prices may vary tremendously. The goal of this work is to analyze in detail the generation technologies, their strategies and energy mix to gain awareness and knowledge to evaluate energy price fluctuations. Two methods are used to forecast in different time horizons: ARIMAX and NARX. Both methods are homologous, using historical energy prices and optionally an explanatory variable. Three options are studied: no explanatory, energy demand and competitive market. Once the models are developed and trained, the results achieved are helpful to understand further changes in the market. These energy forecasts are competent to schedule energy generation and/or consumption. Keywords: Energy Market, Forecasting, Time Series JEL Classifications: C5.1; L1.1